EFFECTIVENESS OF TOTAL LEUKOCYTE COUNT (TLC) AND C-REACTIVE PROTEIN (CRP) IN THE DIAGNOSIS OF ACUTE APPENDICITIS - IQBAL, I; KHAN, G; MEMON, ZA; NISAR, U; KHAN, U; KHAN, S; ARIF, M; SIDDQIUI, FG; RAJPUT, IA; KHAN, NA (Biological and Clinical Sciences Research Journal, 2024)
Acute appendicitis is a typical surgical emergency. Diagnosing it can be challenging due to variable symptoms. Total leukocyte count (TLC) and C-reactive protein (CRP) are commonly used to assess inflammation and guide treatment. This study evaluates the diagnostic accuracy of TLC and CRP in acute appendicitis to determine appropriate management. Objective: This study aimed to assess the diagnostic accuracy of TLC and CRP in predicting acute appendicitis and their role in determining the proper management approach, either conservative or surgical. Methods: This prospective observational cohort study was conducted in the Department of General Surgery at Dow University of Health Sciences (DUHS), Ojha Campus, from July 2023 to March 2024. A total of 87 adult patients with clinical signs of appendicitis and an Alvarado score of greater than 4 were enrolled. Data was analyzed using SPSS version 22. Variables included socio-demographic characteristics, clinical presentations, and levels of TLC and CRP. Both conservative and surgical management approaches were analysed, with laparoscopic appendectomy being the most common procedure. Results: Among the 87 patients, most were male. TLC and CRP levels were similar across genders, with notable variations in socio-demographic characteristics. CRP levels were more frequently elevated in patients managed conservatively compared to those managed surgically. Both TLC and CRP were elevated in 43 patients (49.4%), highlighting the value of using both markers together. Surgical intervention, primarily laparoscopic appendectomy, was the preferred treatment, with suppurative inflammation being the most common histopathological finding. Conclusion: The combination of TLC and CRP significantly improves the diagnostic accuracy for acute appendicitis. TLC correlates more strongly with the need for surgical intervention, whereas CRP did not show a significant association with management type. Both markers are useful in assessing the duration of the complaint, but they are not substitutes for clinical judgment. Further research is warranted to refine their diagnostic utility and evaluate their impact on surgical care availability in resource-limited settings.